Climate influences on whitebark pine mortality from mountain pine beetle in the Greater Yellowstone Ecosystem. Issue 8 (30th September 2016) - Buotte, Polly C.; Hicke, Jeffrey A.; Preisler, Haiganoush K.; Abatzoglou, John T.; Raffa, Kenneth F.; Logan, Jesse A.
Abstract: Extensive mortality of whitebark pine, beginning in the early to mid‐2000s, occurred in the Greater Yellowstone Ecosystem (GYE) of the western USA, primarily from mountain pine beetle but also from other threats such as white pine blister rust. The climatic drivers of this recent mortality and the potential for future whitebark pine mortality from mountain pine beetle are not well understood, yet are important considerations in whether to list whitebark pine as a threatened or endangered species. We sought to increase the understanding of climate influences on mountain pine beetle outbreaks in whitebark pine forests, which are less well understood than in lodgepole pine, by quantifying climate–beetle relationships, analyzing climate influences during the recent outbreak, and estimating the suitability of future climate for beetle outbreaks. We developed a statistical model of the probability of whitebark pine mortality in the GYE that included temperature effects on beetle development and survival, precipitation effects on host tree condition, beetle population size, and stand characteristics. Estimated probability of whitebark pine mortality increased with higher winter minimum temperature, indicating greater beetle winter survival; higher fall temperature, indicating synchronous beetle emergence; lower two‐year summer precipitation, indicating increased potential for host tree stress; increasing beetle populations; stand age; and increasing percent composition of whitebark pine within a stand. The recent outbreak occurred during a period of higher‐than‐normal regional winter temperatures, suitable fall temperatures, and low summer precipitation. In contrast to lodgepole pine systems, area with mortality was linked to precipitation variability even at high beetle populations. Projections from climate models indicate future climate conditions will likely provide favorable conditions for beetle outbreaks within nearly all current whitebark pine habitat in the GYE by the middle of this century. Therefore, when surviving and regenerating trees reach ages suitable for beetle attack, there is strong potential for continued whitebark pine mortality due to mountain pine beetle.